Improving Simple Writing Skills Through The Use Of Image Series Media In Class Ii Students At SDN Sondakan Laweyan Surakarta - Hirawati, Agustina Nurfri (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this study is to improve writing skills in a simple essay by applying media image series. Media picture series directs students to be active in learning. Writing skills need to be mastered since elementary school education.  This research is in the form of Classroom Action Research (PTK) with two cycles. PTK carried out in this study consisted of four stages, namely: 1) planning; 2) implementation; 3) observation; 4) reflection. The subjects of this study were the students of Class II of Sondakan Laweyan Elementary School, totaling 28 students. This study uses data collection techniques such as interviews, observation, tests, and documentation. Analysis of the data used is the Miles-Huberman interactive analysis model. The results of simple essay writing skills of students in class II before the action showed 36% classically. Cycle 1 produces a percentage of 61% classically. The study continued with cycle 2 with an achievement percentage of 86% classically. Actions that have been carried out in each cycle have increased the percentage of achievement in simple essay writing skills. Thus the application of series drawing media can improve writing skills in a simple essay.